2012
DOI: 10.1111/j.1365-2184.2012.00812.x
|View full text |Cite
|
Sign up to set email alerts
|

Sox2 targets cyclinE, p27 and survivin to regulate androgen‐independent human prostate cancer cell proliferation and apoptosis

Abstract: Sox2 expression is necessary for cell proliferation and evasion of apoptosis in prostate cancer cells and TGF-α could regulate Sox2 and survivin expression by activating the EGFR/PI3K/AKT pathway.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
51
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(61 citation statements)
references
References 38 publications
9
51
1
Order By: Relevance
“…6C; Supplementary Fig. S1; data not shown), Ki67 positivity was not dependent on the SOX2 expression level, which is in contrast to findings in other tumor entities (11,17).…”
Section: Sox2 Modulates Csc Properties In Human Soc Cellscontrasting
confidence: 52%
See 3 more Smart Citations
“…6C; Supplementary Fig. S1; data not shown), Ki67 positivity was not dependent on the SOX2 expression level, which is in contrast to findings in other tumor entities (11,17).…”
Section: Sox2 Modulates Csc Properties In Human Soc Cellscontrasting
confidence: 52%
“…More recently, enhanced SOX2 expression has been detected in several epithelial tumors (6,7,(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19) suggesting that SOX2 also regulates tumorigenesis. On the basis of its prominent role in pluripotent stem cell stemness, SOX2 expression has been proposed as a general feature of CSCs (12,27,29,44).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this connection, SOX2 is able to down-regulate OCT-4, but not vice versa. Moreover, several recent studies have shown that an important relationship exists between AKT pathway activation and SOX2, OCT-4, NANOG, and self-renewal capacity (33,34). In our study, SW1736 showed a constitutive expression of p-AKT, confirming the relationship between AKT and the self-renewal-related markers SOX2 and OCT4.…”
supporting
confidence: 71%